2020
DOI: 10.1002/aelm.202000932
|View full text |Cite
|
Sign up to set email alerts
|

Near‐Infrared Organic Phototransistors with p‐Channel Photosensitive Layers of Conjugated Polymer Composed of bis‐Octyldodecyl‐Diketopyrrolopyrrole and Benzothiadiazole Units

Abstract: A near‐infrared (NIR)‐absorbing conjugated polymer, poly[{2,5‐bis‐(2‐octyldodecyl)‐3,6‐bis‐(thien‐2‐yl)‐pyrrolo[3,4‐c]pyrrole‐1,4‐diyl}‐co‐{2,2′‐(2,1,3‐benzothiadiazole)‐5,5′‐diyl}] (PODTPPD‐BT), which is synthesized via a Stille coupling reaction, can play a dual role (charge transport and sensing) in NIR‐sensing organic phototransistors (OPTRs). The PODTPPD‐BT films, which feature two strong optical absorption peaks at wavelengths (λ) of 830 and 935 nm, possess a highly ordered crystalline state as evidenced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Here, it is worthy to note that the device current was relatively higher at the thicker PDPP-8OBT films, which can be attributed to the increased volume for charge transport as typically measured for sheet resistances of films. [26][27][28][29] Accordingly, as shown in Figure 2b (bottom panel), the electrical resistance (R H ) of devices was restricted to 4-6 TΩ even at 60 V, which complies with the low resistance requirement of LDRs. [30][31][32][33] In more detail, as displayed in Figure 2c (top panel), the specific electrical resistance (R HS,D ) of devices in the dark condition reached %20-40 EΩ cm À2 in the presence of slight deviations according to the film thickness and applied voltage.…”
Section: Resultssupporting
confidence: 61%
“…Here, it is worthy to note that the device current was relatively higher at the thicker PDPP-8OBT films, which can be attributed to the increased volume for charge transport as typically measured for sheet resistances of films. [26][27][28][29] Accordingly, as shown in Figure 2b (bottom panel), the electrical resistance (R H ) of devices was restricted to 4-6 TΩ even at 60 V, which complies with the low resistance requirement of LDRs. [30][31][32][33] In more detail, as displayed in Figure 2c (top panel), the specific electrical resistance (R HS,D ) of devices in the dark condition reached %20-40 EΩ cm À2 in the presence of slight deviations according to the film thickness and applied voltage.…”
Section: Resultssupporting
confidence: 61%
“…The photoresponsivity ( R C ), which is the ratio of net drain current under light ( I D,Light – I D,Dark ) to the incident light intensity ( P IN ), gradually decreased with the incident light intensity, irrespective of the wavelength. This trend reflects that the degree of charge recombination in the PIDTT-NDI layers became higher as the incident light intensity increased. Finally, the continuous sensing characteristics were tested for the OFETs with the PIDTT-NDI PCLs ( t = 100 nm) upon optical on–off modulations of incident light. As shown in Figure , the drain current obviously changed according to the light-on and light-off states, irrespective of wavelengths.…”
Section: Resultsmentioning
confidence: 99%
“…Park et al reported a near‐infrared organic phototransistor with a p‐channel based on poly(diketopyrrolopyrrole‐benzothiadiazole) (PDPPBT) with a narrow bandgap. [ 137 ] In thin films, close contact between DPP units can cause strong dipole interactions between carbonyl groups and nearby nitrogen atoms. Therefore, evenly distributed charge transfer complexes were formed in the crystalline domain of the channel layer to promote the photoresponse.…”
Section: Application Of Phototransistors In Artificial Synapses and P...mentioning
confidence: 99%